IMPACT OF ONLINE SHOPPING ADVERTS ON CONSUMER BUYING RATE - Mr. P. Anbarasan ,Dr. Magdalene Peter (Journal of Computational Analysis and Applications (JoCAAA), 2024)
The Tamil Nadu retail market has undergone tremendous transformation as a result of therecent surge in internet shopping and consumers interest purchasing in online. Today mostlythey were accepted to change. In online shopping, festive days like "Big Billion Day" Sale on Flipkart is an illustration of how customers buying behavior are evolving.